Poverty, protest and sport: poaching in the East Midlands c.1820-1900 - Muge, Rosemary (2018)
In the East Midlands counties of Derbyshire, Leicestershire and Nottinghamshire levels of poaching equalled or exceeded those in many counties which are thought of as prime poaching areas.Using principally Criminal Registers, Game Laws Returns to Parliament, and local newspapers of the period, this study shows that people poached from three motives: because they were poor; because poaching was a sport; and as a protest. Day and night poachers,including night poaching gangs frequently involved in affrays, pursued their activities undeterred by the efforts at prevention of the landowners, police and courts. Poaching here was predominantly for ground game and declined in the last quarter of the century, but continued to be a source of anger and frustration for game preservers and the authorities to the end of this period. The poaching war in these counties, waged in an area with large aristocratic estates but where extreme game preservation was viewed critically, was not perceived as impacting on law and order in general. This was unlike Lancashire, where the activities of poachers were regarded as being a threat to the fabric of society. The causes of these differences between the East Midlands and Lancashire were rooted in police practice, attitudes to game preservation, and differences in gentry sport and hunting.